Pecking Order and Static Trade-Off Models of Capital Structure: An Empirical Examination of Sri Lankan Listed Companies - Kengatharan, L.; Koperunthevy, K. (JOURNAL OF EMERGING FINANCIAL MARKETS AND POLICY, VOL. 1, NO. 1, MARCH 2022, 2022)
This study examines the applicability of pecking order and static trade-off models of capital structure to Sri Lankan listed companies. Using data for 103 non-financial companies from 2007/08 to 2016/17, we test the two models employing the Generalized Method of Moment method. We find that the magnitude of the relation between the financing deficit and change in debt is very low, and firms finance only a small portion of their financing requirement through debt, providing weak support to the pecking order model. Although more profitable as well as larger firms prefer less debt inconsistent with the trade-off model, high-growth firms seem to use less debt consistent with the trade-off model, giving weak evidence to support the trade-off model as well. The pecking order model seems more applicable because listed companies consider external debt finance when meeting the financing deficit.
Keywords: Capital structure; Debt ratio; Pecking order model; Trade-off model; SriLanka